2015
DOI: 10.1016/j.aaspro.2015.08.080
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Resistance Genes to Leaf Rust Lr34 And Lr37 in Wheat Germplasm

Abstract: Gene pyramiding is a breeding strategy whereby host resistance genes are combined together with the objective of prolonging their usefulness in crops such as wheat (Triticum aestivum) for resistance to leaf rust caused by Puccinia recondita f.sp. tritici. When genes are combined they often give reactions different from those given by each component gene alone. Effects of gene combinations in lines Lr13 + Lr34 (T34-13), Lr13 + Lr37 (T13-37) and Lr34 + Lr37 (T34-37) were compared with those of the single gene li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…However, Mago et al (2005) reported that the Sr24/ Lr24 gene is extensively deployed in Australian wheat cultivars. The frequency of Lr37 observed in the present study was lower than that reported previously by Cristina et al (2015) who observed a frequency of 40%. The low frequency of Lr37 observed in the present study indicated that most of the tested genotypes lack the Triticum ventricosum fragment, which was introduced into Triticum aestivum from Aegilops ventricosa Tausch.…”
Section: Genotyping Of Rust Resistance Genescontrasting
confidence: 90%
“…However, Mago et al (2005) reported that the Sr24/ Lr24 gene is extensively deployed in Australian wheat cultivars. The frequency of Lr37 observed in the present study was lower than that reported previously by Cristina et al (2015) who observed a frequency of 40%. The low frequency of Lr37 observed in the present study indicated that most of the tested genotypes lack the Triticum ventricosum fragment, which was introduced into Triticum aestivum from Aegilops ventricosa Tausch.…”
Section: Genotyping Of Rust Resistance Genescontrasting
confidence: 90%
“…f. sp. tritici) (Cristina, Turcu, & Ciuca, 2015). The area under the disease-progress curve (AUDPC) of the two varieties ranged within 30-92.5.…”
Section: Resultsmentioning
confidence: 99%
“…The dried pellets were resuspended in 50 µl TE buffer (10 mM Tris, 1 mM ethylenediaminetetraacetic acid (EDTA), pH 8.0) and incubated at 42 • C for 2 h to facilitate the dissolution of DNA. DNA from barley grains was extracted using a modified sodium dodecyl sulfate (SDS) extraction protocol from Cristina et al [32]. 30 mg of finely ground barley grains were suspended in 500 µl lysis buffer (2.5% sorbitol (w/v), 100 mM Tris, 50 mM EDTA, 500 mM NaCl, 2% sodium N-laurylsarcosinate (w/v), 1% sodium dodecylsulfate (SDS) (w/v)).…”
Section: Quantification and Identification Of Phytopathogenic Fungimentioning
confidence: 99%